2015
DOI: 10.3389/fneur.2015.00242
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Repetitive Sensory Stimulation as Intervention to Improve Sensory Loss in Patients with Complex Regional Pain Syndrome I

Abstract: Achieving perceptual gains in healthy individuals or facilitating rehabilitation in patients is generally considered to require intense training to engage neuronal plasticity mechanisms. Recent work, however, suggested that beneficial outcome similar to training can be effectively acquired by a complementary approach in which the learning occurs in response to mere exposure to repetitive sensory stimulation (rSS). For example, high-frequency repetitive sensory stimulation (HF-rSS) enhances tactile performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…As hypothesized and consistent with previous literature, the CRPS-affected hand displayed poor tactile acuity relative to the CRPS-unaffected hand and pain-free control subjects (Pleger et al, 2006;Maihöfner and DeCol, 2007;Peltz et al, 2011;Lewis and Schweinhardt, 2012;Reiswich et al, 2012;Catley et al, 2014;David et al, 2015). While in healthy control subjects, one might hypothesize that increased use of the dominant hand would result in better tactile acuity than the nondominant hand, we found no difference in dominant and nondominant tactile acuity in control subjects, a result consistent with findings of previous investigations (Gelber et al, 1995;Ozcan et al, 2004;Pleger et al, 2006;Tustumi et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As hypothesized and consistent with previous literature, the CRPS-affected hand displayed poor tactile acuity relative to the CRPS-unaffected hand and pain-free control subjects (Pleger et al, 2006;Maihöfner and DeCol, 2007;Peltz et al, 2011;Lewis and Schweinhardt, 2012;Reiswich et al, 2012;Catley et al, 2014;David et al, 2015). While in healthy control subjects, one might hypothesize that increased use of the dominant hand would result in better tactile acuity than the nondominant hand, we found no difference in dominant and nondominant tactile acuity in control subjects, a result consistent with findings of previous investigations (Gelber et al, 1995;Ozcan et al, 2004;Pleger et al, 2006;Tustumi et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, future studies should evaluate the difference in tactile acuity assessment via discrimination and temporal order judgment tasks to understand whether different tactile assessments can lead to different tactile acuity outcomes and relationships with GABA. This is important in a clinical setting, given that tactile acuity training reportedly helps to improve tactile acuity as well as reduce pain intensity in CRPS (David et al, 2015;Schmid et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HF-rSS significantly improved tactile discrimination on the treated hand in 16 patients and pain relief by more than 30% was reported in only 4 patients. However, Authors suggested that longer treatment periods might be required to induce consistent pain relief (27). In this way the electro-analgesic therapy is a novel neuro-modulatory approach using electro-cutaneous nerve stimulation of no pain information that interferes with pain signals.…”
Section: Treatmentmentioning
confidence: 99%
“…[9][10][11][12] Additionally, a recent nonrandomised study using high-frequency repetitive sensory long-term potentiation (LTP)-like stimulation suggested it could reduce sensory impairment in patients with CRPS. 13 To date, no RCTs have investigated the effect of TENS on sensorimotor performance in patients with CRPS. However, it has been shown that TENS relieves phantom pain and facilitates perceptual embodiment of prosthetic limbs, 14 when TENS sensation is projected into the phantom limb itself.…”
Section: Introductionmentioning
confidence: 99%